2001
DOI: 10.1002/1522-2683(200107)22:12<2490::aid-elps2490>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Capillary zone electrophoresis for the characterization of latex particles

Abstract: Capillary zone electrophoresis (CZE) was applied to the separation of acrylic styrene copolymer emulsion particles. Fast separations could be performed on samples containing chemically identical latex particles of different size, as well as on samples with particles of the same size but differing in chemical composition. The developed method was also used for the analysis of water soluble fractions of urethane dispersions. Additionally, the physical interaction between different particles (e.g., acrylic and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Among these techniques is capillary electrophoresis (CE) which has been used in the analysis of viruses and bacteria [3,4], liposomes [5], gold colloid [6], and polymer microspheres [7]. Among these particles gold colloid and microspheres are expected to be homogeneous and thus good models to study the electrophoretic behavior of particles in the presence of an electric field.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Among these techniques is capillary electrophoresis (CE) which has been used in the analysis of viruses and bacteria [3,4], liposomes [5], gold colloid [6], and polymer microspheres [7]. Among these particles gold colloid and microspheres are expected to be homogeneous and thus good models to study the electrophoretic behavior of particles in the presence of an electric field.…”
Section: Introductionmentioning
confidence: 78%
“…Multiple reports have clearly confirmed that polystyrene latex microspheres have an intrinsic electrophoretic mobility that makes them amenable to analysis by CE [7,11]. This fact is confirmed in Fig.…”
Section: Electropherograms Of Individually Detected Microspheresmentioning
confidence: 96%
See 3 more Smart Citations